Popping into Focus: Community Engagement for Environmental Impact and Awareness - Daepp, Madeleine; Fitzmaurice, Helen; Janzen, Shawn; Ponce, Jaime; Roseway, Asta; Felkner, Juliana; Copfer, Wende; Pinfold, Wilfred; Niyogi, Dev (2020)
An eerie orange sky along North America’s West Coast heralds a “new normal” that, scientists have warned, will be marked by increasingly frequent and severe weather events including wildfires, droughts, and extreme precipitation (Lustgarten, 2020). In the absence of intervention, climate change is predicted to contribute in excess of 150 million needless premature deaths due to air pollution over the next 40 years (Shindell et al., 2018), reinforcing preexisting social and economic disparities in respiratory disease burdens (Krieger, 2011). Within the next 70 years, rising sea levels could displace another 150 million people globally (Kulp & Strauss, 2019) and more than 10 million people in the United States (Hauer, 2016), reshaping housing landscapes within and between cities (Boustan et al., 2020; Keenan, Hill & Gumber, 2018). Heat waves will become more common, exacerbating urban heat island effects (IPCC, 2014, p. 109) that disproportionately affect historically redlined neighborhoods in the U.S. (Hoffman, Shandas, & Pendleton, 2020) and rapidly urbanizing cities globally (IPCC, 2014, p. 932).